(untitled) (Transport systems and technologies, 2022)
To increase the efficiency of operation of the hopper car, it is proposed to improve it by dividing the body into two separate sections, which facilitates the possibility of transporting different types of cargo. In order to adapt the hopper car for transportation on railway ferries in international traffic, it is proposed to install on its pivot beams knots for fastening chain ties. Determination of the dynamic load of the load-bearing structure of the hopper car was performed by mathematical modeling. The case of the on-board rocking of the railway ferry is taken into account. The solution of the mathematical model is implemented in the MathCad software package. The total amount of acceleration acting on the supporting structure of the hopper car was 2.4 m/s2 (0.24 g). The obtained value of acceleration is taken into account when calculating the strength of the load-bearing structure of the hopper car. The calculation was performed by the finite element method in the SolidWorks Simulation software package. The results of the calculations established that the maximum equivalent stresses are 312.3 MPa and occur in the node for fixing. However, they do not exceed the allowable values. The conducted researches will promote increase of efficiency of operation of hopper cars, and also creation of developments concerning designing of their perspective designs.